F44 Disentangling apathy subtypes in huntington's disease: a white matter biomarker of disease profile and progression. (September 2018) - Paepe, Audrey E De; Sierpowska, Joanna; García-Gorro, Clara; Martinez-Horta, Saül; Perez-Perez, Jesus; Kulisevsky, Jaime; Rodriguez-Dechicha, Nadia; Vaquer, Irene; Subira, Susana; Calopa, Matilde; Muñoz, Esteban; Santacruz, Pilar; et al.
Abstract : Along with motor and cognitive deterioration, neuropsychiatric symptoms form a common feature of Huntington's disease. Of these, apathy has been shown to most highly correlate with disease progression, often emerging prior to clinical diagnosis. However, due to the multidimensional nature of apathy, its elusive etiology, and the lack of operative diagnostic criteria, treatment options are limited. The present study combine diffusion tensor imaging (DTI) with precise apathy scales to investigate the relationship between white matter microstructural change and apathy in premanifest (n=22) and early manifest Huntington's disease (n=24) compared with controls (n=35).Global apathy was measured using both the short Problem Behavior Assessment and the Lille Apathy Rating Scale, short-form. Principle component analysis of the LARS-s produced three apathy subtypes: emotional, cognitive, and auto-activation deficit. We found that premanifest participant's portrayed significantly higher auto-activation deficit apathy, with early manifest patients additionally showing significantly increased apathy in cognitive apathy as well as global apathy. Analysis by DTI showed a significant rightward disturbance in the uncinate fasciculus (UF), the frontostriatal tract (FST), and the dorsolateral prefrontal cortex to caudate nucleus tract (dlPFC-cn). Importantly, specific apathy subtypes were found to be associated with discrete tracts. Specifically, higher levels of subtype-specific apathy correlated with a lateralized decrease in structural connectivity in the dlPFC-cn and FST for the cognitive domain of apathy and in the UF for auto-activation deficit, predominantly on the right side. That apathy subtypes are associated with distinct white matter substrates supports the importance of an individualized approach to its diagnosis and treatment.